Capacidad antioxidante de papaya (Carica papaya), mango (Mangifera indica) y elaboración de una compota enriquecida con camu camu (Myrciaria dubia) - Ushiñahua Ojanama, Eliane Shantal (2024)
This research was carried out in the facilities of the Pilot Canning Plant of the F.I.A., being the raw materials: papaya, mango and camu camu, with the main objective being to find the method of free radical sequestration using the DPPH method (2,2 diphenyl -1- picril-hydrazil) expressed as (μmol TE/100 g. ms): 1.08, 11.23 and 38.67, the % of inhibition was also determined, being the average values; 59.95%. 25.85% and 61.26% the content of total phenols expressed (mg GAE/g.ms) as gallic acid having values of papaya: 0.22, mango, 0.086 camu camu, 12.70, as for the compote enriched with vitamin C, subsequently a standard method was reached, having certain coincidences in the stages of the process. Subsequently, the physicochemical analyses of the three proposed treatments were carried out, plus a blank sample: T0, T1, T2 and T3: moisture: 87.94 g, 87.85 g, 87.73 g, 86.90 g, ash: 0.16 g, 0.17 g, 0.16 g, 0.21 g, proteins: 0.65 g, 0.35 g, 0.30 g, 0.26 g, carbohydrates: 11.15g, 11.41g, 11.80 g, 12.53 g, fat: 0.10 g, 0.22g, 0.01 g, 0.10g, titratable acidity (citric acid): 0.35%, 0.35%, 0.38%, 0.28%, pH(20oC): 6.10, 6.11, 6.07 and 6.23, soluble solids: 9.00, 15.00, 17.50, 18.00, energy (Kcal): 48.10, 49.02, 48.49 and 52.02, dry matter: 12.06 g, 12.15 g, 12.27g, 13.10 g., vitamin C: 0 mg, 130.00 mg, 131.00 mg and 132.00 mg. In relation to microbiological analysis, the three treatments are within the range for human consumption and in the statistical evaluations there is no difference between each treatment.